Farmers’ Motivation In Mendong Farming - Suyudi Suyudi; H.M. Iskandar Mamoen (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
Manonjaya subdistrict as a production center for the Mendong plant, a plantation commodity crop as a source of raw material for the tannery, crafts and handy craft industries. This research was conducted to determine the motivation level of Mendong farmers and to analyze the Correlation between physiological needs, security needs, social needs, appreciation needs and self-actualization with the motivation of Mendong farmers. This research was conducted in Manonjaya Subdistrict, Tasikmalaya District. The research method was carried out by surveying the cases of mendong farmers. In this study, it was used to analyze the level of motivation of Mendong farmers. Descriptive analysis using scoring techniques. Furthermore, to determine the Correlation between motivational factors of Mendong farmers, Chi Square analysis with 2 x 2 contingency tables was carried out. The results showed that the motivation level of Mendong farmers in Kamulyan Village, Manonjaya subdistrict, Tasikmalaya district, from the total overall score was in the high category, 867 in number. However, for each farmer's level of motivation, physiological needs, social needs and self-actualization factors are in the high category, while the need for security and the need for appreciation is in the low category. Social needs and self-actualization factors are related to the motivation of mendong farmers, while the factors of physiological needs, security needs and reward needs have no Correlation with the motivation of the mendong farmers.